Assessment of the Correlation between BMI, Waist Circumference, and the Snacking Pattern and Dairy Consumption among Female Student Residents of Shiraz University Dormitories - Shiva Faghih (Women’s Health Bulletin, 2014)
Background: It is suggested that the type and frequency of snacks as well as dairy consumption can influence body weight and composition. Objectives: This study attempts to assess the correlation of BMI and waist circumference with snacking pattern and dairy consumption among female university students. Materials and Methods: We randomly selected 112 female students who were residents of Shiraz University dormitories as participants in this cross-sectional study. Weight, height and waist circumference of the participants were measured. Demographic and food frequency questionnaires were completed in face-to-face interviews. Data were analyzed using SPSS version 16. Results: The results showed that 17% of participants were underweight, 74.1% were normal weight and 8.9% were overweight. Among participants, 95.5% had a normal waist circumference whereas the waist circumference in 4.5% was above normal. There were 63.3% of female students who consumed just one snack per day. Confectionaries (84.1%) were the most popular snacks. Mean ± SD dairy consumption was 1.78 ± 1.20 servings per day. There were no correlations between body mass index and waist circumference with snacking pattern or dairy intake. Conclusions: The majority of our subjects had normal weight and waist circumference, thus we did not find any correlation between body mass index and waist circumference to snacking pattern or dairy intake. Similar studies should be conducted that enroll both overweight and normal weight subjects.